Checking in on grammar checking. (18th April 2016) - DALE, ROBERT
Abstract: Ten years ago, Microsoft Word's grammar checker was really the only game in town. The software world, and the world of natural language processing, have changed a lot in that time, so what does the grammar checker marketplace have to offer today?